Vorticity screening by dense layers - Forrest W. Doss (AIP Advances, 2022)
We investigate variable density layers in the presence of vortices, by analogy to line charges in the presence of a dielectric slab. We adapt solutions for dielectric layers from the literature to the variable density fluid case, obtaining exact hypergeometric expressions for flow velocities induced everywhere by a vortex in the vicinity of a finite-thickness slab of different densities. The dimensionless Atwood number, which appears naturally in other variable density phenomena, such as the Rayleigh–Taylor instability, reappears here as the natural ordering parameter for the influence of the slab, which acts primarily to screen the influence of vorticity across the slab to a lower effective circulation. The solution takes the form of scaling correction factors that might be applied to computational models or evaluated directly. Extensions, where vorticity is localized within the dense layer itself and amplified outside of it, are considered, as well as some speculative applications such as inertial confinement fusion capsule designs.